A randomized comparison of cold snare polypectomy versus a suction pseudopolyp technique - Din, Said; Ball, Alex J.; Riley, Stuart A.; Kitsanta, Panagiota; Johal, Shawinder (Endoscopy, 2015)
Background: Cold snare techniques are widely used for removal of diminutive and small colorectal polyps. The influence of resection technique on the effectiveness of polypectomy is unknown. We therefore compared standard cold snare polypectomy with a newly described suction pseudopolyp technique, for completeness of excision and for complications.Patients and methods: In this single-center study, 112 patients were randomized to cold snare polypectomy or the suction pseudopolyp technique. Primary outcome was endoscopic completeness of excision. Consensus regarding the endoscopic assessment of completeness of excision was standardized and aided by chromoendoscopy. Secondary outcomes included: completeness of histological excision, polyp “fly away” and retrieval rates, early bleeding (48 hours), delayed bleeding (2 weeks), and perforation. Results: 148 polyps were removed, with size range 3 – 7 mm, 60 % in the left colon, and 90 % being sessile. Regarding completeness of excision (with uncertain findings omitted): endoscopically, this was higher with the suction pseudopolyp technique compared with cold snare polypectomy but not statistically significantly so (73/74 [98.6 %] vs. 63/68 [92.6 %]; P = 0.08). A trend towards a higher complete histological excision rate with the suction pseudopolyp technique was also not statistically significant (45/59 [76.3 %] vs. 37/58 [63.8 %]; P = 0.14). Polyp retrieval rate was not significantly different (suction 68/76 [89.5 %] vs. cold snare 64/72 [88.9 %]; P = 0.91). No perforation or bleeding requiring hemostasis occurred in either group. Conclusion: In this study both polypectomy techniques were found to be safe and highly effective, but further large multicenter trials are required.Clinical trial registration at www.clinicaltrials.gov: NCT02208401